2020
DOI: 10.3390/molecules25092228
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Ensembles of Protein Tertiary Structures Generated De Novo via Clustering

Abstract: Controlling the quality of tertiary structures computed for a protein molecule remains a central challenge in de-novo protein structure prediction. The rule of thumb is to generate as many structures as can be afforded, effectively acknowledging that having more structures increases the likelihood that some will reside near the sought biologically-active structure. A major drawback with this approach is that computing a large number of structures imposes time and space costs. In this paper, we propose a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…USRs were shown to be highly accurate at describing and comparing molecular shapes. Work in [ 18 ] further showed that USR coordinates were highly useful for low-dimensional representations of protein tertiary structures, and a body of work utilized them to build fast, search space-aware algorithms for exploring and reconstructing the structure space of a protein molecule [ 19 , 20 ], as well as computing motion paths connecting two given structures of a protein molecule [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…USRs were shown to be highly accurate at describing and comparing molecular shapes. Work in [ 18 ] further showed that USR coordinates were highly useful for low-dimensional representations of protein tertiary structures, and a body of work utilized them to build fast, search space-aware algorithms for exploring and reconstructing the structure space of a protein molecule [ 19 , 20 ], as well as computing motion paths connecting two given structures of a protein molecule [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using this procedure, the docked ligands, namely, retinol and PS, are ranked according to the docking score. The ligand poses obtained from AutoDock Vina are further analyzed using gmx-cluster algorithm in the GROningen MAchine for Chemical Simulations package . The centroid structures of PS obtained from the gmx-cluster were used as the starting point for the MD simulations.…”
Section: Methodsmentioning
confidence: 99%
“…The long-range interactions were treated with the Particle Mesh Ewald (PME) method. The Lennard-Jones potentials were used for van der Waals interactions [ 35 ]. The distance cut-off of 10.0 Å was applied to calculate the nonbond interactions.…”
Section: Methodsmentioning
confidence: 99%